IN-VITRO ASSESSMENT OF THE THERAPEUTIC POTENTIAL OF POLYMYXINS AND TIGECYCLINE AGAINST MULTIDRUG-RESISTANT ACINETOBACTER ISOLATES FROM INFECTED WOUNDS - Khurshid, Mohsin; Rashid, Abid; Husnain, Muhammad; Rasool, Muhammad Hidayat; Waqas, Umair; Saeed, Muhammad; Naeem, Muhammad; Sohail, Muhammad (Journal of Ayub Medical College Abbottabad, 2020)
Background: The incidence of multidrug-resistant (MDR), extreme drug resistant (XDR), and pan drug-resistant (PDR) Acinetobacter are increasing throughout the world. The therapeutic management and control of Acinetobacter are difficult due to the emergence of drug resistance and its enduring capacity to survive in the environment. The present study was designed to appraise the efficacy of Polymyxins and Tigecycline against multidrug-resistant Acinetobacter isolates from surgical and burn wounds. Methods: During the study, the specimens were collected from various types of wounds from inpatients and outpatients of the tertiary care hospitals of Lahore, Pakistan in 2017 and 2018. The bacterial pathogens were isolated and identified using standard microbiological procedures and molecular confirmation of Acinetobacter species was examined by PCR using specific primers. The antibiotic susceptibility profiling of Acinetobacter isolates was studied against 18 antibiotics as per Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: The Acinetobacter isolates demonstrated extreme resistance especially to ampicillin/sulbactam, piperacillin/tazobactam, cephalosporins, carbapenems, fluoroquinolones, and aminoglycosides. However, the colistin, polymyxin, and tigecycline remained the most effective antimicrobial agents against Acinetobacter isolates. Conclusion: The results highlight the extent of drug resistance and therapeutic potential of Polymyxins and Tigecycline for wound infections caused by MDR and XDR Acinetobacter species. The wiser use of antimicrobials, incessant surveillance of antimicrobial resistance, and stringent adherence to infection control guidelines are critical to reducing major outbreaks in the future. Keywords: Acinetobacter; Wounds; Antimicrobial resistance; Polymyxins; Tigecycline